2002
DOI: 10.1161/hq0102.101129
|View full text |Cite
|
Sign up to set email alerts
|

Metalloproteinase Inhibition and the Response to Angioplasty and Stenting in Atherosclerotic Primates

Abstract: Abstract-Determinants of restenosis after angioplasty include constrictive remodeling and intimal hyperplasia. Both processes require extensive matrix turnover, so matrix metalloproteinases (MMPs) have become potential targets of antirestenosis therapies. We studied the effects of RO113-2908, a broad-spectrum MMP inhibitor (MMPI), on the response to iliac artery angioplasty and stenting in atherosclerotic cynomolgus monkeys. Lumen diameter (LD) was measured angiographically, and artery wall geometry was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 56 publications
1
23
0
1
Order By: Relevance
“…However, small molecule MMP inhibitors fail to prevent restenosis, even though they efficiently block early smooth muscle cell migration (Bendeck et al, 1996). Recently, the broad spectrum MP inhibitor RO113-2908 failed to prevent angioplasty-or stent-induced intermal hyperplasia over 4 weeks in atherosclerotic primates (Cherr et al, 2002), although MP inhibitors do reduce constrictive remodeling in a porcine angioplasty model (de Smet et al, 2000). Similarly, TIMP overexpression (Cheng et al, 1998;Dollery et al, 1999;Forough et al, 1996) prevented smooth muscle cell migration but long-term benefits were not fully established.…”
Section: Mmp Blockade and Cardiovascular Diseasementioning
confidence: 99%
“…However, small molecule MMP inhibitors fail to prevent restenosis, even though they efficiently block early smooth muscle cell migration (Bendeck et al, 1996). Recently, the broad spectrum MP inhibitor RO113-2908 failed to prevent angioplasty-or stent-induced intermal hyperplasia over 4 weeks in atherosclerotic primates (Cherr et al, 2002), although MP inhibitors do reduce constrictive remodeling in a porcine angioplasty model (de Smet et al, 2000). Similarly, TIMP overexpression (Cheng et al, 1998;Dollery et al, 1999;Forough et al, 1996) prevented smooth muscle cell migration but long-term benefits were not fully established.…”
Section: Mmp Blockade and Cardiovascular Diseasementioning
confidence: 99%
“…7,8) We herein have shown that ONO-4817 could inhibit the atherosclerotic neointimal hyperplasia in experimental hyperlipidemic rabbits.…”
Section: Discussionmentioning
confidence: 73%
“…In previous studies 7,8) and a recent study by RS-130830, 9) it was reported that intimal hyperplasia could not be attained by these drugs. The inhibitory activity of RS-130830 and ONO-4817 is summarized in Table. 9,10) The balance of inhibitory activity, not the strength of inhibitory activity, may explain the inhibition of intimal hyperplasia.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations